Patai's Chemistry of Functional Groups 2009
DOI: 10.1002/9780470682531.pat0250
|View full text |Cite
|
Sign up to set email alerts
|

Silyl Migrations

Abstract: Introduction 1,2‐Silyl Migrations 1,3‐Silyl Migrations 1, N ‐Silyl Migrations ( n  ≥ 4)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 457 publications
0
2
0
Order By: Relevance
“…This type of isomerization to a bridging diazoalkyl ligand is unknown for transition metal systems, though it has been seen with lanthanides and uranium. 3235 The known aluminum complex [(CH(SiMe 3 ) 2 )Al(μ-NNC(SiMe 3 ))] 2 has the same CNN bridging core, but its trimethylsilyl group is coordinated to carbon. 31 …”
mentioning
confidence: 99%
“…This type of isomerization to a bridging diazoalkyl ligand is unknown for transition metal systems, though it has been seen with lanthanides and uranium. 3235 The known aluminum complex [(CH(SiMe 3 ) 2 )Al(μ-NNC(SiMe 3 ))] 2 has the same CNN bridging core, but its trimethylsilyl group is coordinated to carbon. 31 …”
mentioning
confidence: 99%
“…Reduction of the ketone with NaBH 4 gave the corresponding alcohol with >10 : 1 diastereoselectivity as determined by NMR analysis. 19 After some experimentation, it was found that methylation of the newly generated hydroxyl-group could be performed on gram scale by deprotonation with a freshly prepared precooled solution of LiHMDS followed by alkylation with methyl triflate (MeOTf) at -78 • C. Allowing the reaction mixture to warm resulted in a significant amount of 1,3-silyl migration 20 and a mixture of products. Selective removal of the primary TBS-group 21 in 12 and oxidation with Dess-Martin periodinane 22 then completed a synthesis of aldehyde 6.…”
mentioning
confidence: 99%